Pengaruh Tingkat Naungan Terhadap Pertumbuhan dan Hasil Bawang Daun (Allium fistulosum L) - Bagyono; Margo Yuwono; Dewi Murni (Fakultas Pertanian Universitas Papua, 2009)
The aim of this experiment was to identify the effect of shading level to the growth and yield of scallion. This experiment was conducted at Amban from October to December 2006. The completed randomized design was used in this study consisting of three shading levels as a treatment : 35 %, 60 % including no-shading as a comparison (control) in 20 replicates. The result showed that plants with 35 % and 60 % shading levels had higher plant than none shading. Scallion in this study was found more tolerant to 35 % shading level, while 60 % shading level caused decreasing in leaf number, shoot number and length of wild branch. Shading level of 35 % decreased fresh weight up to 29.45 % and stem diameter about 21.57 %, while 60 % shade reduced fresh weight and stem diameter for about 27.08 % and 37.72 %, respectively.